The impact of revolving door practice and policy on nonprofessional investors' perceptions of auditor independence. Issue 7 (10th November 2017) - Wilson, Reginald
Abstract : This study investigates whether an ex-auditor's employment with an audit client impairs nonprofessional investors' perceptions of auditor independence, and whether the strength of the US revolving door policy improves their perceptions of auditor independence. Despite nonprofessional investors owning over one-third of the US equity holdings, the literature has not examined how revolving door policy impacts their perceptions of auditor independence. Two between-subjects experiments examine these issues. The first experiment finds that investors perceive the ex-auditor's integrity to be significant in explaining the firm's decision to manage earnings, irrespective of the firm's previous working relationship with the ex-auditor. The results from experiment two indicate that strengthening the revolving door policy above that of the American Institute of Certified Public Accountants' policy does not improve perceptions of auditor independence. Academics may be interested in triangulating the independence 'in appearance' results of this study to the independence 'in fact' results of other studies, since the Securities and Exchange Commission asserts that both facets of independence are equally important. The results may also be of interest to academics and practitioners, as prior research suggests that restricting auditors' moves to management positions with the client impairs firms' abilities to hire quality auditors.